On Some Applications of Matrix Partial Orders in Statistics - Iva Golubić; Janko Marovt (International School for Social and Business Studies, 2020)
In statistics different partial orders appear as useful in several cases. Three of the best known partial orders defined on (sub)sets of real or complex matrices are the Löwner, the minus and the star partial orders. Another two matrix partial orders that are related to the star partial order are the leftstar and the right-star partial orders. In the paper we review some of the applications of mentioned partial orders in statistics.